Implementasi Kebijakan Pemerintah Tanzania Terhadap Convention on the Rights of Persons with Disabilities (CRPD) Pada Kasus Albinnisme Tahun 2009-2024 - Rachmawati, Anita; Trisnaningtyas, Januari Pratama Nurratri (Global and Policy Journal of International Relations, 2025)
ABSTRACT Tanzanian society faces cases related to human security, especially against the albinism group. The existence of supersititious beliefs that are still developing, especially those spread by witch doctors, causes albinism to become victims of exploitation ranging from human trafficking, violence, to discrimination which ends up threatening the safety and welfare of Tanzanian albinism. This growing shamanic practice contributes to the high number of cases of assault, kidnapping, and even murder of albinism, both by the general public and their own families. In response, the Tanzanian government ratified the the Convention on the Rights of Persons with Disabilities (CRPD) in 2009 as an effort to legally protect and sanction perpetrators of discrimination against albinism. This research aims to analyse the Tanzanian govermment’s implementation of the CRPD in addressing cases of violence against albinism in 2009-2024 using compliance theory with three indicators: outputs, outcomes, and impacts. The method used is qualitative with data collection techniques from books, official reports, journal articles, and media publications. The result showed that despite a decrease in cases in some years, attack on albinism still fluctuate until 2024. Keywords: CRPD Implementation, Albinism Tanzania, Human Security, Albinism DiscriminationABSTRAK Masyarakat Tanzania menghadapi kasus terkait human security khususnya terhadap kelompok albinisme. Adanya kepercayaan terhadap tahayul yang masih berkembang, terutama yang disebarkan oleh para dukun, menyebabkan albinisme menjadi korban dari tindakan eksploitasi mulai dari perdagangan manusia, kekerasan, hingga diskriminasi yang berakhir pada ancaman keselamatan dan kesejahteraan dari albinisme Tanzania. Praktik perdukunan yang berkembang ini berkontribusi pada tingginya kasus penyerangan, penculikan, bahkan pembunuhan terhadap albinisme, baik yang dilakukan oleh masyarakat umum maupun keluarga sendiri. Sebagai tanggapan, pemerintah Tanzania meratifikasi Convention on the Rights of Persons with Disabilities (CRPD) pada tahun 2009 sebagai upaya perlindungan hukum dan pemberian sanksi bagi pelaku diskriminasi kepada albinisme. Penelitian ini bertujuan untuk menganalisis implementasi CRPD oleh pemerintah Tanzania dalam menangani kasus kekerasan terhadap albinisme pada tahun 2009-2024 dengan menggunakan teori kepatuhan dengan tiga indikator: outputs, outcomes, dan impacts. Metode yang digunakan adalah kualitatif dengan teknik pengumpulan data dari buku, laporan resmi, artikel jurnal, dan media publikasi. Hasil penelitian menunjukkan bahwa maskipun telah terjadi penurunan kasus pada bebrapa tahun, serangan terhadap albinisme masih terjadi secara fluktuatif hingga tahun 2024. Kata Kunci: Implementasi CRPD, Albinisme Tanzania, Keamanan Manusia, Diskriminasi Albinisme